2009
DOI: 10.1016/j.rgg.2008.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and seismic effects in the ice cover of Lake Baikal

Abstract: The mechanics of the ice cover of Lake Baikal has been studied through monitoring of its deformation and seismic effects and full-size uniaxial compression and shear tests in 2005–2007. We measured the shear strength of ice specimens and large in situ blocks (σ = 0.2−1.9 MPa) and investigated it as a function of air temperature and ice structure. Deformation was analyzed in terms of various natural controls, such as air temperature and pressure, wind, sub-ice currents, and local earthquakes. Precise strain mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 3 publications
1
16
0
Order By: Relevance
“…Some land‐terminating glaciers may generate low‐magnitude events due to thermal cracking of ice on marginal lakes nearby [ Carmichael et al , ]. Interestingly, multiyear passive seismic observations of the mechanical behavior of Lake Baikal ice provided a basis for treating it as a model for large‐scale lithospheric processes [ Ruzhich et al , ].…”
Section: Sea/lake Ice and Icebergsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some land‐terminating glaciers may generate low‐magnitude events due to thermal cracking of ice on marginal lakes nearby [ Carmichael et al , ]. Interestingly, multiyear passive seismic observations of the mechanical behavior of Lake Baikal ice provided a basis for treating it as a model for large‐scale lithospheric processes [ Ruzhich et al , ].…”
Section: Sea/lake Ice and Icebergsmentioning
confidence: 99%
“…The equivalent magnitudes of seismic events at lakes are only M w = 0.2 ∼ 0.8 [Ruzhich et al, 2009;Carmichael et al, 2012]. Nevertheless, it was recently shown that thermal cracking of lake ice can induce strong vibrations in coastal high-rise buildings [Makkonen et al, 2010].…”
Section: Lake Icementioning
confidence: 99%
“…Naively, icequakes should not occur because the critical patch size for nucleation is much greater than the lake ice thickness. Yet icequakes clearly nucleate on temperate lakes (Ruzhich et al, ). The slip law for friction provides insight, ∂ψ∂t=VslipψDslipln[]VslipψVref=VslipψDslipln[]ψψss where P eff = P ref is the ambient pressure to compact notation and the second equality applies the steady state value of ψ in equation .…”
Section: Thermal Weakening Of Asperity Tips In Icementioning
confidence: 99%
“…For context, warm ice on the Earth clearly behaves in a macroscopically ductile manner as at low strain rates within glaciers (e.g., Barnes et al, 1971). At high strain rates, icequakes occur as within temperate freshwater lake ice (Ruzhich et al, 2009) and at the base of glaciers (Barruol et al, 2013;Wiens et al, 2008). Snow below 250 K squeaks when stepped upon indicating brittle failure (Patitsas, 2015).…”
Section: Slow Slip On Faults Within Cold Icementioning
confidence: 99%
“…The full scale investigations of the ice cover behavior under the effect of different dynamic loads are very laborious, while temporal instability, variety of behav ior properties, and dependence of these properties on rapidly changing ice conditions additionally aggravate the obtaining of statistically valid results. It was shown in (Ruzhich et al, 2009;Timofeev et al, 2010) that the main causes of deforming and cracking for the ice in Lake Baikal are temperature changes and strong winds, and the submarine currents as well. The associ ated seismic phenomena resemble the manifestations of earthquakes or rock bumps.…”
Section: Introductionmentioning
confidence: 99%